1992
DOI: 10.1364/ao.31.003020
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of blood flow at ocular fundus by using laser speckle

Abstract: We report a method for noninvasively evaluating blood flow at the ocular fundus by using laser speckle phenomena. The intensity fluctuation of speckles scattered from a 1-mm-diameter illuminated area at the fundus is detected and analyzed by the photon-correlation technique, which gives us the relative degree of total blood flows within the probe area. The method is used to evaluate blood flows at the ocular fundus of a rabbit and normal human volunteers. The experimental results show that the present laser sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Located on the smooth surface are two point scatterers, s distance apart and centered about . The light scattered by these two points is observed normally in a plane located at some distance L. From wave optics, we know that the light scattered from each point will interfere in the observation plane and result in an intensity ͑fringe͒ pattern, I(x), given by I͑x ͒ϰ2ϩ2 cos͑kϫoptical path difference͒, (8) where k is the wave number. From Figure 10, the path difference for the two scatterers is ͉͑r 1 ϩr 1 Ј͉͒Ϫ͉͑r 2 ϩr 2 Ј͉͒ϭ͉͑r 2 Ϫr 1 ͉͒Ϫ͉͑r 2 Јϩr 1 Ј͉͒.…”
Section: Advantages and Limitations Of The Imaged Speckle Strain Gaugementioning
confidence: 99%
See 1 more Smart Citation
“…Located on the smooth surface are two point scatterers, s distance apart and centered about . The light scattered by these two points is observed normally in a plane located at some distance L. From wave optics, we know that the light scattered from each point will interfere in the observation plane and result in an intensity ͑fringe͒ pattern, I(x), given by I͑x ͒ϰ2ϩ2 cos͑kϫoptical path difference͒, (8) where k is the wave number. From Figure 10, the path difference for the two scatterers is ͉͑r 1 ϩr 1 Ј͉͒Ϫ͉͑r 2 ϩr 2 Ј͉͒ϭ͉͑r 2 Ϫr 1 ͉͒Ϫ͉͑r 2 Јϩr 1 Ј͉͒.…”
Section: Advantages and Limitations Of The Imaged Speckle Strain Gaugementioning
confidence: 99%
“…1,2 In biomedical applications, its use has not been as extensive, yet several authors have reported on the use of laser speckle for evaluating strains in biological hard tissues, [3][4][5] for imaging variations in local mechanical properties in soft tissue that is being modulated at acoustic frequencies, 6 and for tissue structure monitoring, 7 among other applications, mostly those that involve blood flow. 8 Most of the speckle-based strain measurements in hard biological tissues such as bone have relied upon classical interferometric techniques, such as electronic speckle pattern interferometry ͑ESPI͒, 3 speckle photography, 4 and speckle interferometry. 5 Speckle interferometric methods have not been entirely successful in the quantitative investigation of strain patterns in soft tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Dunn et al 6 also studied cerebral blood-flow imaging using speckles. After that, various studies on speckle blood-flow imaging have been reported including blood flow in skin tissue and retina by Fujii et al [7][8][9][10][11] , Fercher et al 12 , Briers et al 13 , and Aizu et al [14][15][16][17][18] . Other studies have been also presented on performance improvement and animal experiments [19][20][21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
“…1,[4][5][6] In situations where the speckle pattern are produced by scatterers with varying velocities, the activation patterns of the moving scatterers can be more appropriately obtained from a study of the temporal statistics of the speckle fluctuations. 8 Briefly, when coherent light such as from a laser is reflected off a diffuse surface a specular pattern is formed.…”
Section: Introductionmentioning
confidence: 99%